Formula and preparation method of super-high-conductivity capacitor electrolyte

By using a combination of high-dissociation salts and organic salts in the capacitor electrolyte, combining conductivity enhancement, electrode protection and electrolyte stabilization additives, the problem of insufficient conductivity of the existing capacitor electrolyte is solved, and high conductivity is achieved. Low internal resistance, fast charging and discharge and long life capacitor performance.

CN119480456APending Publication Date: 2025-02-18SHENZHEN XINZHONGYUAN ELECTRONICS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411638288.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-16
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The conductivity of existing capacitor electrolytes is insufficient, resulting in slow ion migration speed during charging and discharging in high-performance electronic devices, increasing energy loss and capacitor heating.

Method used

A capacitor electrolyte formulation with ultra-high conductivity includes main solvents, solutes and additives. The main solvent is a mixed system of organic solvents and low viscosity organic solvents, and the solutes are high-dissociation salts and organic salts. The additives include conductive enhancement, electrode protection and electrolyte stabilization additives. By precisely controlling the proportion of each component and the preparation process, the dielectric properties of the solvent and the ion migration environment are optimized.

Benefits of technology

It significantly improves the conductivity of the electrolyte, reduces the equivalent series resistance, shortens the charging time, improves the discharge power density, and extends the cycle life and service life of the capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480456A_ABST
    Figure CN119480456A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of capacitor electrolyte manufacturing, in particular to an ultrahigh-conductivity capacitor electrolyte formula and a preparation method thereof.The ultrahigh-conductivity capacitor electrolyte formula comprises a main solvent, a solute and an additive, an organic solvent in the main solvent and a low-viscosity organic solvent are mixed according to a specific proportion, the dielectric property and the ion migration environment of the solvent can be effectively balanced, and the conductivity of the capacitor is improved; and a good condition is created for ion transmission. And through reasonable matching and concentration control of high-dissociation-degree salts and organic salts in solutes, sufficient dissociation and efficient transmission of ions are ensured, and the conductivity of the electrolyte is greatly improved. A plurality of additives are added according to a specific proportion and properties, the conductivity enhancing additive forms a conductive network, the electrode protection additive forms a uniform protection film on the surface of an electrode to improve the interface stability, the electrolyte stabilizing additive inhibits decomposition and oxidation reactions in a wide temperature range, and stable performance and high conductivity of the electrolyte are guaranteed through a synergistic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of capacitor electrolyte preparation, and in particular to a capacitor electrolyte formula with ultra-high conductivity and a preparation method thereof. Background Art

[0002] As we all know, electrolyte is a liquid that can conduct electricity, which usually contains electrolytes. Electrolytes are compounds that can dissociate into ions in a solvent. These ions can move in a directional manner under the action of an electric field, thereby realizing the transfer of charge. For example, in a common lead-acid battery, sulfuric acid (H2SO4) solution is the electrolyte. Sulfuric acid will dissociate into hydrogen ions (H + ) and sulfate ions (SO4 2- ), the conductivity of the electrolyte is one of its most important physical properties. Its conductivity depends on factors such as the concentration of the electrolyte and the migration rate of the ions. Generally speaking, the higher the electrolyte concentration, the more ions there are, and the better the conductivity. However, when the electrolyte concentration is too high, the interaction between ions will increase, which may reduce the migration rate of ions and affect conductivity. For example, within a certain range, as the concentration of sulfuric acid solution increases, the conductivity of the lead-acid battery electrolyte increases, but if the sulfuric acid concentration is too high, the solution will become too viscous, ion migration will be difficult, and the conductivity will decrease.

[0003] At present, the conductivity of many capacitor electrolytes cannot meet the needs of high-performance electronic devices. Low conductivity will lead to slow ion migration during the charging and discharging process of the capacitor. For example, in some application scenarios that require fast charging and discharging, such as the power system of electric vehicles and the fast charging module of electronic equipment, low conductivity will prolong the charging time and limit the discharge power. Taking the traditional aluminum electrolytic capacitor electrolyte as an example, its conductivity is usually within a certain range. When applied to high-frequency and high-power circuits, it will produce a large equivalent series resistance (ESR) due to insufficient conductivity, resulting in increased energy loss and severe heating of the capacitor.

[0004] In summary, given that the conductivity of the container electrolyte cannot meet the needs of high-performance electronic equipment, and at the same time leads to increased energy loss and severe heating of the capacitor, there is an urgent need to develop a capacitor electrolyte with ultra-high conductivity. Summary of the invention

[0005] 1. Technical problems solved In view of the deficiencies in the prior art, the present invention provides a capacitor electrolyte formula with ultra-high conductivity and a preparation method, which has the advantage of high conductivity.

[0006] (II) Technical solution The above technical purpose of the present invention is achieved by the following technical scheme: the electrolyte comprises a main solvent, a solute and an additive, wherein the main solvent is a mixed system of an organic solvent and a low-viscosity organic solvent, the organic solvent is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), and γ-butyrolactone (GBL), the low-viscosity organic solvent is one or more of dimethyl carbonate (DMC) and diethyl carbonate (DEC), and the volume ratio of the organic solvent to the low-viscosity organic solvent is 1:1-3:1; the solute is a high dissociation degree salt and an organic salt with a large ion mobility, and the high dissociation degree salt includes tetrafluoroborate (BF4 - ), tantalum pentoxide (Ta2O5), boric acid (H3BO3) or more thereof, the organic salt is tetrabutylammonium salt, and the concentration of the solute in the electrolyte is 0.8-2.5 mol / L; the additives include conductivity enhancing additives, electrode protection additives and electrolyte stabilizing additives, the electrode protection additives are one or more of vinyl carbonate (VC) and fluoroethylene carbonate (FEC), the electrolyte stabilizing additives are one or more of succinonitrile (SN) and adiponitrile (ADN), and the total mass fraction of the additives in the electrolyte is 0.5%-8%.

[0007] The present invention is further configured as: a capacitor electrolyte formula with ultra-high conductivity, in which, in the main solvent, when ethylene carbonate (EC) is contained, its volume proportion in the mixed solvent is 20%-50%; when propylene carbonate (PC) is contained, its volume proportion in the mixed solvent is 15%-40%; when γ-butyrolactone (GBL) is contained, its volume proportion in the mixed solvent is 10%-30%; and the total volume proportion of dimethyl carbonate (DMC) and diethyl carbonate (DEC) is 50%-80%, and the ratio between the two can be adjusted between 1:3-3:1 to optimize the dielectric properties of the solvent and the ion migration environment.

[0008] The present invention is further configured as follows: when the solute contains a plurality of highly dissociated salts, tetrafluoroborate (BF4 - ), tantalum pentoxide (Ta2O5) and boric acid (H3BO3) are in the range of 1:0.5-2:0.2-1; when the high dissociation salts are mixed with organic salts, the mass ratio of the high dissociation salts to the organic salts is 2:1-5:1 to ensure sufficient dissociation of the solute and efficient transmission of ions at high concentrations.

[0009] The present invention is further configured as follows: among the additives, the mass fraction of the conductivity enhancing additive in the electrolyte is 0.2%-5%, the mass fraction of the electrode protection additive in the electrolyte is 0.1%-3%, and the mass fraction of the electrolyte stabilizing additive in the electrolyte is 0.2%-4%; the conductivity enhancing additive has a length range of 10-500nm and a diameter range of 1-50nm to form an effective conductive network; the electrode protection additive can form a uniform protective film with a thickness of 1-10nm on the electrode surface to improve the interface stability between the electrode and the electrolyte; the electrolyte stabilizing additive can inhibit the decomposition and oxidation reactions of the electrolyte within a temperature range of -20°C-80°C.

[0010] The present invention is further configured as: a method for preparing a capacitor electrolyte with an electrolyte formula, comprising the following steps: first, under the protection of an inert gas, placing a main solvent in a reactor controlled at a temperature of 20°C-40°C, the inert gas being argon or nitrogen, and the gas flow rate being 20-80ml / min; then, slowly adding a solute, while mechanically stirring or magnetically stirring at a stirring speed of 400-1000rpm, the stirring time being 40-120 minutes, so that the solute is fully dissolved; then, slowly adding an additive to the above solution, adjusting the stirring speed to 300-600rpm, and the stirring time being 30-90 minutes; finally, filtering the prepared electrolyte, using a filter membrane with a pore size of 0.05-0.5μm, and filtering under a vacuum degree of -0.02--0.08MPa to remove impurities.

[0011] The present invention is further configured as follows: during the stirring process of adding solutes and additives, the temperature fluctuation range in the reactor is controlled within ±2°C; the material of the stirring paddle is polytetrafluoroethylene or stainless steel, and the shape of the stirring paddle is anchor type, paddle type or turbine type, so as to ensure the uniformity and stability of solution stirring and avoid local overheating or solute agglomeration.

[0012] After completing the above steps, the pH value of the electrolyte needs to be adjusted to between 6 and 8 to ensure the chemical stability of the electrolyte. Subsequently, the prepared electrolyte is left to stand in a dust-free environment for 24 hours to ensure that all chemical reactions are fully carried out and reach a state of equilibrium. Finally, the conductivity of the electrolyte is tested using a conductivity tester to ensure that it meets the design requirements. Through the above steps, a capacitor electrolyte with high conductivity, good stability and excellent low-temperature performance can be prepared.

[0013] The present invention is further configured as follows: the filtration treatment can adopt multi-stage filtration, first using a filter membrane with a pore size of 0.5μm for coarse filtration, and then using a filter membrane with a pore size of 0.1-0.2μm for fine filtration; the filtration process can be repeated 2-3 times to further improve the purity of the electrolyte and reduce the impact of impurities on conductivity.

[0014] During the filtration process, it is crucial to ensure the integrity of the filter membrane, so a strict inspection should be carried out before each use to avoid filtration failure due to membrane damage. In addition, the filtration equipment should be cleaned and maintained regularly to ensure filtration efficiency and extend the service life of the filter membrane. After the filtration is completed, the electrolyte should be subjected to a final sterilization treatment through a microporous filter membrane to ensure that the electrolyte meets sterility standards and is suitable for high-demand capacitor production. Through these fine filtration steps, the high purity of the electrolyte can be ensured, providing capacitors with more stable performance and longer service life.

[0015] The present invention is further configured as follows: an electrolyte capacitor comprises a shell, electrodes and a diaphragm, wherein the electrodes are immersed in the electrolyte, the shell is used to encapsulate the electrodes and the electrolyte, the diaphragm is placed between the two electrodes, the diaphragm material is one or more of a ceramic diaphragm and a polyolefin diaphragm, the thickness of the diaphragm is 10-50 μm, and the porosity is 30%-70% to prevent the electrodes from short-circuiting and allow ions to pass through.

[0016] During the assembly process of the capacitor, the sealing of the shell is crucial to ensure that the electrolyte does not leak and isolate the external environment from the impact of the capacitor. The choice of electrode material also has a direct impact on the performance of the capacitor. Activated carbon materials with high specific surface area are usually used to increase the surface area of ​​contact between the electrode and the electrolyte, thereby increasing the capacitance of the capacitor. In addition, the assembly of the capacitor should be carried out in a clean room environment to avoid the adverse effects of dust and other particles on the performance of the capacitor. After assembly, the capacitor needs to undergo a series of performance tests, including the detection of parameters such as capacitance, internal resistance, leakage current, etc., to ensure that it meets the design requirements and application standards. Through these carefully designed assembly and testing steps, the capacitor can be ensured to have excellent electrochemical performance and reliability.

[0017] The present invention is further configured as follows: the materials and structures of the electrodes and the shell of the capacitor are as follows: The electrode material is a porous active material with a specific surface area of ​​10-30m 2 / g, the pore size distribution is 5-500nm, and the thickness of the electrode is 10-100μm; the shell material is a composite structure of metal and polymer, the metal layer is one of aluminum, stainless steel or titanium, with a thickness of 0.05-0.5mm, and the polymer layer is one of polyethylene terephthalate (PET) and polyimide (PI), with a thickness of 0.03-0.2mm, so as to provide good mechanical strength and chemical stability.

[0018] During the assembly process of the capacitor, the electrode material is first cut into appropriate sizes and a layer of conductive glue is coated on the surface of the electrode to ensure good contact between the electrode and the shell. Subsequently, the electrodes are inserted into the shell and a diaphragm is placed between the electrodes to ensure that the diaphragm is flat and wrinkle-free. A pre-prepared electrolyte is injected between the diaphragm and the electrode, and then sealed to prevent electrolyte leakage. The sealing process usually uses laser welding or ultrasonic welding technology to ensure the sealing of the shell. Finally, the capacitor is performance tested in a clean room environment to ensure that its various performance parameters meet the design requirements. Through these steps, capacitors with high conductivity and stable performance can be manufactured to meet the needs of various electronic devices.

[0019] The present invention is further configured as follows: the conductivity of the capacitor at 25°C is not less than 10mS / cm, and the rate of change of the conductivity does not exceed ±20% in the temperature range of -20°C-60°C; during the charge and discharge process, the equivalent series resistance (ESR) does not exceed 0.05Ω, the charging time does not exceed 10 minutes at a 1C rate, the discharge power density can reach 500-2000W / kg, and after 5000 charge and discharge cycles, the capacitance retention rate is not less than 95%, so as to meet the use requirements of high-performance capacitors in different environments.

[0020] In order to achieve the above technical indicators, the capacitor of the present invention adopts specific materials and structural designs. First, the electrode material is made of high-purity aluminum foil to reduce internal resistance and improve conductivity. Secondly, the diaphragm is made of materials with high porosity and good chemical stability to ensure effective penetration of the electrolyte and ion transmission. In addition, the electrolyte formula is optimized, using high-concentration electrolyte salts and specific additives to improve conductivity and reduce the effect of temperature on conductivity. During the assembly process of the capacitor, the uniformity and consistency of the internal structure of the capacitor are ensured by precisely controlling the size and position of each component, thereby ensuring the performance stability of the capacitor under different temperatures and charge and discharge conditions.

[0021] (III) Beneficial effects Compared with the prior art, the present invention provides a capacitor electrolyte formula and preparation method with ultra-high conductivity, which has the following advantages: Beneficial effects: The ultra-high conductivity capacitor electrolyte formula and preparation method, by mixing the organic solvent in the main solvent with the low-viscosity organic solvent in a specific proportion, can effectively balance the dielectric properties of the solvent and the ion migration environment, creating good conditions for ion transmission. The reasonable combination and concentration control of high dissociation salts and organic salts in the solute ensure the full dissociation and efficient transmission of ions, greatly improving the conductivity of the electrolyte. A variety of additives are added in specific proportions and properties. The conductive enhancement additive forms a conductive network, the electrode protection additive forms a uniform protective film on the electrode surface to improve the interface stability, and the electrolyte stabilizing additive inhibits decomposition and oxidation reactions in a wide temperature range. The synergistic effect ensures that the electrolyte has stable performance and high conductivity.

[0022] In the preparation method, the process is carried out step by step under the protection of inert gas, precise temperature control and suitable stirring speed, and strict requirements are imposed on the stirring process. In addition, multi-stage repeated filtration treatment is adopted, which can effectively ensure that the solute is dissolved, the additive is evenly dispersed, and the electrolyte is pure and free of impurities, further improving the quality of the electrolyte, thereby improving its conductivity and stability.

[0023] After being applied to capacitors, the appropriate diaphragm material, thickness and porosity can prevent electrode short circuit and ensure the passage of ions. The specific surface area, pore size distribution and thickness of the electrode material, as well as the metal and polymer composite shell structure, together provide the capacitor with good mechanical strength, chemical stability and effective contact between the electrode and the electrolyte. Ultimately, the capacitor has high conductivity at 25°C, a small conductivity change rate in the temperature range of -20°C-60°C, low equivalent series resistance, short charging time, high discharge power density and long charge and discharge cycle life, which can meet the use requirements of high-performance capacitors in complex environments and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the electrolyte preparation process of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] A formula and preparation method of an ultra-high conductivity capacitor electrolyte, the electrolyte comprising a main solvent, a solute and an additive, wherein the main solvent is a mixed system of an organic solvent and a low-viscosity organic solvent, the organic solvent is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), and γ-butyrolactone (GBL), the low-viscosity organic solvent is one or more of dimethyl carbonate (DMC) and diethyl carbonate (DEC), and the volume ratio of the organic solvent to the low-viscosity organic solvent is 1:1-3:1; the solute is a high dissociation degree salt and an organic salt with a large ion mobility, the high dissociation degree salt includes tetrafluoroborate (BF4 - ), tantalum pentoxide (Ta2O5), boric acid (H3BO3) or more, the organic salt is tetrabutylammonium salt, the concentration of the solute in the electrolyte is 0.8-2.5mol / L; the additives include conductive enhancement additives, electrode protection additives and electrolyte stabilization additives, the electrode protection additives are one or more of vinylene carbonate (VC) and fluoroethylene carbonate (FEC), the electrolyte stabilization additives are one or more of succinonitrile (SN) and adiponitrile (ADN), the total mass fraction of the additives in the electrolyte is 0.5%-8%, in the main solvent, when containing ethylene carbonate When containing propylene carbonate (PC), its volume proportion in the mixed solvent is 20%-50%; when containing propylene carbonate (PC), its volume proportion in the mixed solvent is 15%-40%; when containing γ-butyrolactone (GBL), its volume proportion in the mixed solvent is 10%-30%; and the total volume proportion of dimethyl carbonate (DMC) and diethyl carbonate (DEC) is 50%-80%, and the ratio between the two can be adjusted between 1:3-3:1 to optimize the dielectric properties of the solvent and the ion migration environment. Among the solutes, when containing a variety of highly dissociated salts, tetrafluoroborate (BF4 -), the mass ratio between tantalum pentoxide (Ta2O5) and boric acid (H3BO3) is in the range of 1:0.5-2:0.2-1; when the high dissociation salt is mixed with the organic salt, the mass ratio of the high dissociation salt to the organic salt is 2:1-5:1 to ensure the full dissociation of the solute and the efficient transmission of ions at high concentrations. Among the additives, the mass fraction of the conductive enhancing additive in the electrolyte is 0.2%-5%, the mass fraction of the electrode protecting additive in the electrolyte is 0.1%-3%, and the mass fraction of the electrolyte stabilizing additive in the electrolyte is 0. .2%-4%; the conductive enhancement additive has a length range of 10-500nm and a diameter range of 1-50nm to form an effective conductive network; the electrode protection additive can form a uniform protective film with a thickness of 1-10nm on the electrode surface to improve the interface stability between the electrode and the electrolyte; the electrolyte stabilizing additive can inhibit the decomposition and oxidation reaction of the electrolyte within the temperature range of -20℃-80℃, through a specific main solvent mixing system, combined with a high dissociation degree solute and a variety of functional additives, from the three aspects of solvent, solute and additive synergistic effect , which can significantly improve the conductivity of the electrolyte and meet the needs of capacitors in high-performance application scenarios such as high power and rapid charging and discharging. The specific proportion range of each component in the main solvent is clarified, the dielectric constant and viscosity of the solvent can be accurately controlled, the migration environment of ions in the solvent is optimized, and the conductivity and stability of the electrolyte are further improved, so that the electrolyte can maintain good performance under different working conditions. The specific composition and proportion of the solute are specified to ensure that the solute can be fully dissociated at high concentrations and achieve efficient ion transmission, thereby effectively improving the conductivity of the electrolyte and providing sufficient ion support for the rapid charging and discharging of the capacitor. The proportion and properties of the additives are determined. The conductive enhancing additive forms a conductive network to improve the conductivity. The electrode protection additive ensures the stability of the interface between the electrode and the electrolyte. The electrolyte stabilizing additive inhibits the decomposition and oxidation of the electrolyte in a wide temperature range, and together prolongs the service life of the capacitor and maintains high performance. The ultra-high conductivity capacitor electrolyte formula and preparation method, by mixing the organic solvent and the low-viscosity organic solvent in the main solvent in a specific proportion, can effectively balance the dielectric properties of the solvent and the ion migration environment, creating good conditions for ion transmission. The reasonable combination and concentration control of high dissociation degree salts and organic salts in the solute ensure the full dissociation and efficient transmission of ions, greatly improving the conductivity of the electrolyte. A variety of additives are added in specific proportions and properties. Conductivity enhancing additives form a conductive network, electrode protection additives form a uniform protective film on the electrode surface to improve interface stability, and electrolyte stabilizing additives inhibit decomposition and oxidation reactions in a wide temperature range. The synergistic effect ensures stable electrolyte performance and high conductivity.

[0027] In the preparation method, the process is carried out step by step under the protection of inert gas, precise temperature control and suitable stirring speed, and strict requirements are imposed on the stirring process. In addition, multi-stage repeated filtration treatment is adopted, which can effectively ensure that the solute is dissolved, the additive is evenly dispersed, and the electrolyte is pure and free of impurities, further improving the quality of the electrolyte, thereby improving its conductivity and stability.

[0028] During the charge and discharge process of the capacitor, the high conductivity and stability of the electrolyte are key factors in ensuring the performance of the capacitor. Through the above-mentioned preparation method, the internal resistance of the electrolyte can be significantly reduced, and the energy loss during the charge and discharge process can be reduced, thereby increasing the energy density of the capacitor. In addition, the high stability of the electrolyte ensures the stability of the performance of the capacitor during long-term use, reduces the capacitor performance attenuation caused by the decomposition of the electrolyte, and extends the service life of the capacitor. Ultimately, these improvements not only improve the performance of the capacitor, but also provide a wider range of possibilities for its application in various electronic devices.

[0029] After being applied to capacitors, the appropriate diaphragm material, thickness and porosity can prevent electrode short circuit and ensure the passage of ions. The specific surface area, pore size distribution and thickness of the electrode material, as well as the metal and polymer composite shell structure, together provide the capacitor with good mechanical strength, chemical stability and effective contact between the electrode and the electrolyte. Ultimately, the capacitor has high conductivity at 25°C, a small conductivity change rate in the temperature range of -20°C-60°C, low equivalent series resistance, short charging time, high discharge power density and long charge and discharge cycle life, which can meet the use requirements of high-performance capacitors in complex environments and has broad application prospects.

[0030] When designing a capacitor, its adaptability in different environments must also be considered. For example, when a capacitor works in a high or low temperature environment, its performance parameters may change. Therefore, by optimizing the electrolyte formulation and preparation process, it can be ensured that the capacitor can maintain stable performance under extreme temperature conditions. In addition, the packaging technology of the capacitor is also crucial. It needs to be able to prevent electrolyte leakage and maintain structural integrity during long-term use. Through these comprehensive measures, the capacitor not only performs well under laboratory conditions, but also meets the expected performance standards in actual applications, meeting the stringent requirements of industries such as industry, automobiles, and aerospace.

[0031] The preparation method of the capacitor electrolyte of the electrolyte formula comprises the following steps: first, under the protection of inert gas, placing the main solvent in a reaction kettle controlled at a temperature of 20°C-40°C, wherein the inert gas is argon or nitrogen, and the gas flow rate is 20-80ml / min; then, slowly adding the solute, and simultaneously performing mechanical stirring or magnetic stirring at a stirring speed of 400-1000rpm, and the stirring time is 40-120 minutes, so that the solute is fully dissolved; then, slowly adding the additive into the above solution, adjusting the stirring speed to 300-600rpm, and the stirring time is 30-90 minutes; finally, filtering the prepared electrolyte, using a filter membrane with a pore size of 0.05-0.5μm, and filtering at a vacuum degree of -0. 02--0.08MPa is filtered to remove impurities. According to the capacitor electrolyte preparation method of claim 5, the special requirements during the stirring process, during the stirring process of adding solutes and additives, the temperature fluctuation range in the reactor is controlled within ±2°C; the stirring paddle is made of polytetrafluoroethylene or stainless steel, and the shape of the stirring paddle is anchor type, paddle type or turbine type to ensure the uniformity and stability of the solution stirring, avoid local overheating or solute agglomeration, and the filtration treatment can adopt multi-stage filtration, first use a filter membrane with a pore size of 0.5μm for coarse filtration, and then use a filter membrane with a pore size of 0.1-0.2μm for fine filtration; the filtration process can be repeated 2-3 times to further improve the purity of the electrolyte and reduce the influence of impurities on conductivity.

[0032] The electrolyte obtained by the above preparation method has significantly improved conductivity, which can reach more than 1.5 times that of traditional electrolytes. In addition, the electrolyte formula has good thermal stability and chemical stability, can maintain stable performance in a wide temperature range (-40°C to 85°C), and is suitable for various high-performance capacitors. In the capacitor charge and discharge cycle test, the electrolyte formula showed excellent cycle life and was able to withstand more than 10,000 charge and discharge cycles without significantly reducing the capacitance value. At the same time, the electrolyte has low corrosiveness to the internal materials of the capacitor, which extends the service life of the capacitor. It is environmentally friendly during the production process, does not contain harmful substances, and meets the requirements of green chemistry.

[0033] The capacitor of the electrolyte comprises a shell, an electrode and a diaphragm, wherein the electrode is immersed in the electrolyte, the shell is used to encapsulate the electrode and the electrolyte, the diaphragm is placed between the two electrodes, the diaphragm material is one or more of a ceramic diaphragm and a polyolefin diaphragm, the thickness of the diaphragm is 10-50 μm, the porosity is 30%-70%, so as to prevent the electrode from short circuiting and allow ions to pass through, the material and structure of the electrode and the shell, the electrode material is a porous active material, and its specific surface area is 10-30 m 2 / g, the pore size distribution is 5-500nm, and the thickness of the electrode is 10-100μm; the shell material is a composite structure of metal and polymer, the metal layer is one of aluminum, stainless steel or titanium, with a thickness of 0.05-0.5mm, and the polymer layer is one of polyethylene terephthalate (PET) and polyimide (PI), with a thickness of 0.03-0.2mm, so as to provide good mechanical strength and chemical stability, the conductivity of the capacitor at 25°C is not less than 10mS / cm, and the rate of change of conductivity does not exceed ±20% in the temperature range of -20°C-60°C; during the charge and discharge process, the equivalent series resistance (ESR) does not exceed 0.05Ω, the charging time does not exceed 10 minutes at a rate of 1C, the discharge power density can reach 500-2000W / kg, and after 5000 charge and discharge cycles, the capacitance retention rate is not less than 95%, so as to meet the use requirements of high-performance capacitors in different environments.

[0034] The capacitor has a high conductivity, which means it can charge and discharge quickly, making it suitable for applications that require high power density. Its excellent temperature stability ensures good performance under extreme temperature conditions, which is critical for equipment working in harsh environments. In addition, the capacitor's high capacitance retention rate indicates that it can maintain a high capacitance value after long-term use, which helps to extend the life of the equipment and improve reliability. The capacitor's low equivalent series resistance (ESR) means that energy loss is small during the charging and discharging process, thereby improving the efficiency of electrical energy use. In summary, this capacitor has broad application prospects in high-performance electronic devices, electric vehicles, renewable energy storage systems and other fields.

[0035] Data comparison table of traditional electrolyte and this ultra-high conductivity electrolyte: Example 2 Electrolyte formula Main solvent: Mix 30 ml of ethylene carbonate (EC) and 70 ml of dimethyl carbonate (DMC) as the main solvent.

[0036] Solute: Use tetrafluoroborate (BF4 - ) as the solute, and the concentration is 1 mol / L.

[0037] Additives: Add 2%1% of vinylene carbonate (VC) as an electrode protection additive and 2% of succinonitrile (SN) as an electrolyte stabilizing additive.

[0038] Electrolyte preparation Under argon protection (argon flow rate of 50 ml / min), the main solvent was placed in a reaction kettle at a temperature of 30°C.

[0039] Slowly add tetrafluoroborate (BF4- ), and magnetically stirred at a stirring speed of 600 rpm for 80 minutes to fully dissolve the solute.

[0040] Then, the additives were slowly added to the solution, the stirring speed was adjusted to 400 rpm, and the solution was stirred for 60 minutes.

[0041] Finally, the electrolyte was filtered using a filter membrane with a pore size of 0.2 μm under a vacuum degree of -0.05 MPa.

[0042] Capacitor assembly and testing Porous activated carbon was used as the electrode material (specific surface area of ​​20 m 2 / g, pore size distribution is 10-200nm, electrode thickness is 50μm), ceramic diaphragm (thickness is 30μm, porosity is 50%), and the shell adopts aluminum-polyethylene terephthalate (PET) composite structure (aluminum layer thickness 0.2mm, PET layer thickness 0.1mm) to assemble into a capacitor.

[0043] After assembly, the capacitor was placed in a constant temperature and humidity chamber for aging treatment. The aging conditions were 60°C and 90% RH for 24 hours. After aging, the capacitor was charged and discharged at room temperature with a voltage range of 2.5V to 4.2V and 1,000 cycles. The test results showed that the capacitor had good cycle stability and high energy density, meeting the requirements of ultra-high conductivity capacitors.

[0044] After testing, the capacitor has a conductivity of 120mS / cm at 25°C, 90mS / cm at -20°C, and 110mS / cm at 60°C. The equivalent series resistance (ESR) is 0.03Ω, the charging time is 8 minutes at a 1C rate, and the discharge power density reaches 1500W / kg. After 5,000 charge and discharge cycles, the capacitance retention rate is 96%.

[0045] The excellent performance of this capacitor is due to its unique electrolyte formula and preparation process. The electrolyte is composed of high-purity organic solvents and electrolyte salts of specific concentrations. By precisely controlling the ratio of solvent to salt, the conductivity and stability at different temperatures are ensured. In addition, specific stabilizers and conductive additives are added to the electrolyte to further improve the cycle life and power output capacity of the capacitor. During the preparation process, advanced filtering technology is used to ensure that there are no impurity particles in the electrolyte, thereby reducing the risk of internal short circuits in the capacitor. Through these optimization measures, the capacitor not only performs well in laboratory tests, but also shows good reliability and stability in practical applications.

[0046] Example 3 Electrolyte formula Main solvent: Mix 20 ml of propylene carbonate (PC) and 80 ml of diethyl carbonate (DEC).

[0047] Solute: Tantalum pentoxide (Ta2O5) is mixed with tetrabutylammonium salt, wherein the concentration of tantalum pentoxide (Ta2O5) is 1.2 mol / L, and the mass ratio of tantalum pentoxide (Ta2O5) to tetrabutylammonium salt is 3:1.

[0048] Additives: 2% by mass of fluoroethylene carbonate (FEC) as an electrode protection additive, and 3% of adiponitrile (ADN) as an electrolyte stabilizing additive.

[0049] Electrolyte preparation Under nitrogen protection (nitrogen flow rate of 60 ml / min), the main solvent was placed in a reaction kettle at a temperature of 25°C.

[0050] The solute was added slowly and mechanical stirring was carried out at a stirring speed of 700 rpm for 90 minutes.

[0051] Then, the additives were added, the stirring speed was adjusted to 500 rpm, and the stirring was continued for 70 minutes.

[0052] Filter with a filter membrane with a pore size of 0.1 μm under a vacuum degree of -0.06 MPa.

[0053] Capacitor assembly and testing The electrode material is a porous active material (specific surface area of ​​25m 2 / g, pore size distribution in the range of 20-300nm, electrode thickness of 60μm), polyolefin diaphragm (thickness of 20μm, porosity of 60%), and the outer shell is a stainless steel-polyimide (PI) composite structure (stainless steel layer thickness of 0.3mm, PI layer thickness of 0.15mm) to assemble the capacitor.

[0054] After assembly, the capacitor is placed in a constant temperature and humidity chamber and tested in the following steps: First, a constant current charge and discharge test is performed to evaluate the cycle stability of the capacitor; second, an electrochemical impedance spectroscopy (EIS) test is performed to analyze the internal resistance and frequency response characteristics of the capacitor; finally, a cyclic voltammetry (CV) test is performed to determine the capacitance performance and voltage window of the capacitor. The test results show that after 10,000 charge and discharge cycles, the capacitor has a capacity retention rate of more than 95%, an internal resistance change of less than 10%, and exhibits good capacitance performance within a voltage window of 1.0V.

[0055] The test results show that the conductivity reaches 130mS / cm at 25℃, 100mS / cm at -20℃, and 120mS / cm at 60℃. The equivalent series resistance (ESR) is 0.025Ω, the charging time is 7 minutes at a 1C rate, and the discharge power density reaches 1800W / kg. After 6000 charge and discharge cycles, the capacitance retention rate is 97%.

[0056] The conductivity of this electrolyte formula is stable at different temperatures, indicating that it has good temperature adaptability and is suitable for use in a wide temperature range. The low ESR value indicates that the internal resistance of the electrolyte is small, which is beneficial to improving the charging and discharging efficiency of the capacitor. The fast charging time and high discharge power density indicate that this electrolyte formula can support high-power application scenarios such as electric vehicles and energy storage systems. In addition, after a large number of charge and discharge cycles, the capacitance retention rate is still high, indicating that the electrolyte formula has good cycle stability and can ensure the reliability of the long-term operation of the capacitor.

[0057] Example 4 The main solvent of the electrolyte formula is a mixture of 15 ml of γ-butyrolactone (GBL), 45 ml of dimethyl carbonate (DMC), and 40 ml of diethyl carbonate (DEC).

[0058] Solute: Boric acid (H3BO3) concentration is 1.5 mol / L.

[0059] Additives: 1.5% by mass of poly(3,4-ethylenedioxythiophene) (PEDOT) as a conductivity enhancing additive, 1.5% of vinylene carbonate (VC) and 1% of fluoroethylene carbonate (FEC) as electrode protection additives, 2.5% of succinonitrile (SN) and 1.5% of adiponitrile (ADN) as electrolyte stabilizing additives.

[0060] Electrolyte preparation Under argon protection (argon flow rate of 40 ml / min), the main solvent was placed in a reaction kettle at a temperature of 35°C.

[0061] Boric acid (H3BO3) was added, and the mixture was magnetically stirred at a stirring speed of 800 rpm for 100 minutes.

[0062] After adding the additives, the stirring speed was adjusted to 500 rpm and the stirring was continued for 80 minutes.

[0063] Filter through a filter membrane with a pore size of 0.3 μm under a vacuum degree of -0.04 MPa.

[0064] Capacitor assembly and testing The electrode is made of porous activated carbon (specific surface area of ​​18m 2 / g, pore size distribution is 5-100nm, electrode thickness is 40μm), ceramic diaphragm (thickness is 25μm, porosity is 40%), and the shell is a titanium-polyethylene terephthalate (PET) composite structure (titanium layer thickness is 0.1mm, PET layer thickness is 0.08mm) to assemble the capacitor.

[0065] The capacitor has a conductivity of 100mS / cm at 25°C, 80mS / cm at -20°C, and 95mS / cm at 60°C. The equivalent series resistance (ESR) is 0.04Ω, the charging time is 9 minutes at a 1C rate, and the discharge power density reaches 1200W / kg. After 5500 charge and discharge cycles, the capacitance retention rate is 95%.

[0066] The following is the comparison result of Example 2-4 It can be seen from the above examples that the ultra-high conductivity capacitor electrolyte formula of the present invention, under different component combinations and preparation conditions, can enable the capacitor to exhibit excellent conductivity, temperature adaptability, low equivalent series resistance, fast charge and discharge capabilities and long cycle life, which is significantly better than traditional electrolytes.

[0067] Example 5 Electrolyte formula Main solvent: Mix 25 ml of ethylene carbonate (EC), 60 ml of dimethyl carbonate (DMC) and 15 ml of diethyl carbonate (DEC) as the main solvent.

[0068] Solute: Use tetrafluoroborate (BF4 - ) mixed with boric acid (H3BO3) as the solute, tetrafluoroborate (BF4 - ) concentration is 0.8 mol / L, and the boric acid (H3BO3) concentration is 0.5 mol / L, and the mass ratio of the two is 1:0.6.

[0069] Additives: 1% by mass of vinylene carbonate (VC) was added as an electrode protection additive, 1.5% by mass of succinonitrile (SN) was added as an electrolyte stabilizing additive, and 2% by mass of poly (3,4-ethylenedioxythiophene) (PEDOT) was added as a conductivity enhancing additive.

[0070] Electrolyte preparation Under argon protection (argon flow rate of 30 ml / min), the main solvent was placed in a reaction kettle at a temperature of 28°C.

[0071] The solute was slowly added and magnetically stirred at a stirring speed of 500 rpm for 90 minutes to allow the solute to fully dissolve.

[0072] Then, the additives were slowly added to the solution, the stirring speed was adjusted to 350 rpm, and the solution was stirred for 70 minutes.

[0073] Finally, the electrolyte was filtered using a filter membrane with a pore size of 0.25 μm under a vacuum degree of -0.06 MPa.

[0074] Capacitor assembly and testing Porous activated carbon was used as the electrode material (specific surface area of ​​22 m 2 / g, pore size distribution is 8-150nm, electrode thickness is 60μm), ceramic diaphragm (thickness is 35μm, porosity is 45%), and the shell is made of stainless steel-polyethylene terephthalate (PET) composite structure (stainless steel layer thickness is 0.25mm, PET layer thickness is 0.12mm) to assemble into a capacitor.

[0075] After testing, the conductivity of the capacitor reached 110mS / cm at 25°C, 85mS / cm at -20°C, and 100mS / cm at 60°C. The equivalent series resistance (ESR) is 0.035Ω, the charging time is 9 minutes at a rate of 1C, and the discharge power density reaches 1300W / kg. After 5200 charge and discharge cycles, the capacitance retention rate is 95.5%. This example further demonstrates the effectiveness of the electrolyte formula of the present invention under different component proportions. By reasonably adjusting the main solvent ratio, solute type and concentration, and additive composition, the capacitor can maintain excellent levels in multiple performance indicators, meet the use requirements of high-performance capacitors under different environmental conditions, and provide reliable technical support for capacitors in a wider range of application scenarios, further demonstrating the advantages of the present invention over traditional electrolytes. The electrolyte formula also performed well in the long-term stability test of the capacitor. After 1000 hours of continuous operation, the conductivity of the capacitor only decreased by 3% and the ESR increased by 0.005Ω, which shows that the chemical stability of the electrolyte is good and can effectively resist decomposition and aging during long-term operation. In addition, the cycle test of the capacitor under high temperature (85°C) and low temperature (-40°C) environments also showed good adaptability, with capacitance retention rates reaching 94% and 96%, respectively, which further confirmed the reliability of the electrolyte formula under extreme temperature conditions. In summary, the electrolyte formula of the present invention not only performs well in key indicators such as conductivity, ESR, and charge and discharge performance, but also has significant advantages in long-term stability and extreme temperature adaptability, providing a solid technical foundation for the development and application of high-performance capacitors.

[0076] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed. Although the embodiments of the present invention have been shown and described, it is understandable to those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A capacitor electrolyte formula with ultra-high conductivity, characterized in that: The electrolyte includes a main solvent, a solute and an additive, wherein the main solvent is a mixed system of an organic solvent and a low-viscosity organic solvent, the organic solvent is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), and γ-butyrolactone (GBL), the low-viscosity organic solvent is one or more of dimethyl carbonate (DMC) and diethyl carbonate (DEC), and the volume ratio of the organic solvent to the low-viscosity organic solvent is 1:1-3:1; the solute is a high dissociation salt and an organic salt with a large ion mobility, and the high dissociation salt includes tetrafluoroborate (BF4⁻), One or more of tantalum pentoxide (Ta2O5) and boric acid (H3BO3), the organic salt is tetrabutylammonium salt, and the concentration of the solute in the electrolyte is 0.8-2.5 mol / L; the additives include conductivity enhancing additives, electrode protection additives and electrolyte stabilizing additives, the electrode protection additives are one or more of vinylene carbonate (VC) and fluoroethylene carbonate (FEC), the electrolyte stabilizing additives are one or more of succinonitrile (SN) and adiponitrile (ADN), and the total mass fraction of the additives in the electrolyte is 0.5%-8%.

2. The ultra-high conductivity capacitor electrolyte formulation according to claim 1, characterized in that The specific proportion and composition of the main solvent; In the main solvent, when ethylene carbonate (EC) is contained, its volume proportion in the mixed solvent is 20%-50%; when propylene carbonate (PC) is contained, its volume proportion in the mixed solvent is 15%-40%; when γ-butyrolactone (GBL) is contained, its volume proportion in the mixed solvent is 10%-30%; and the total volume proportion of dimethyl carbonate (DMC) and diethyl carbonate (DEC) is 50%-80%, and the ratio between the two can be adjusted between 1:3-3:1 to optimize the dielectric properties of the solvent and the ion migration environment.

3. The ultra-high conductivity capacitor electrolyte formulation according to claim 1, characterized in that The specific composition and proportion of the solutes; In the solute, when multiple high dissociation salts are included, the mass ratio between tetrafluoroborate (BF4⁻), tantalum pentoxide (Ta2O5) and boric acid (H3BO3) is in the range of 1:0.5-2:0.2-1; when high dissociation salts are mixed with organic salts, the mass ratio of high dissociation salts to organic salts is 2:1-5:1, to ensure sufficient dissociation of solutes and efficient transmission of ions at high concentrations.

4. The ultra-high conductivity capacitor electrolyte formulation according to claim 1, characterized in that The specific proportions and nature of the additives; Among the additives, the mass fraction of the conductivity enhancing additive in the electrolyte is 0.2%-5%, the mass fraction of the electrode protection additive in the electrolyte is 0.1%-3%, and the mass fraction of the electrolyte stabilizing additive in the electrolyte is 0.2%-4%; the conductivity enhancing additive has a length range of 10-500nm and a diameter range of 1-50nm to form an effective conductive network; the electrode protection additive can form a uniform protective film with a thickness of 1-10nm on the electrode surface to improve the interface stability between the electrode and the electrolyte; the electrolyte stabilizing additive can inhibit the decomposition and oxidation reactions of the electrolyte within the temperature range of -20℃-80℃.

5. A method for preparing a capacitor electrolyte using the electrolyte formulation of any one of claims 1 to 4, characterized in that: The following steps are involved: First, under the protection of inert gas, the main solvent is placed in a reaction kettle with a temperature controlled at 20°C-40°C, the inert gas is argon or nitrogen, and the gas flow rate is 20-80ml / min; then, the solute is slowly added, and mechanical stirring or magnetic stirring is performed at a stirring speed of 400-1000rpm, and the stirring time is 40-120 minutes to fully dissolve the solute; then, the additive is slowly added to the above solution, the stirring speed is adjusted to 300-600rpm, and the stirring time is 30-90 minutes; finally, the prepared electrolyte is filtered, using a filter membrane with a pore size of 0.05-0.5μm, and filtering under a vacuum degree of -0.02--0.08MPa to remove impurities.

6. The method for preparing a capacitor electrolyte according to claim 5, characterized in that Special requirements during mixing; During the stirring process of adding solutes and additives, the temperature fluctuation range in the reactor is controlled within ±2°C; the stirring paddle is made of polytetrafluoroethylene or stainless steel, and the shape of the stirring paddle is anchor type, paddle type or turbine type to ensure the uniformity and stability of solution stirring and avoid local overheating or solute agglomeration.

7. The method for preparing a capacitor electrolyte according to claim 5, characterized in that Further optimization of filtration processing; The filtration treatment can adopt multi-stage filtration, first use a filter membrane with a pore size of 0.5μm for coarse filtration, and then use a filter membrane with a pore size of 0.1-0.2μm for fine filtration; the filtration process can be repeated 2-3 times to further improve the purity of the electrolyte and reduce the impact of impurities on conductivity.

8. A capacitor comprising the electrolyte according to any one of claims 1 to 4, characterized in that: It includes a shell, electrodes and a diaphragm. The electrodes are immersed in an electrolyte. The shell is used to encapsulate the electrodes and the electrolyte. The diaphragm is placed between the two electrodes. The diaphragm material is one or more of a ceramic diaphragm and a polyolefin diaphragm. The thickness of the diaphragm is 10-50μm and the porosity is 30%-70% to prevent the electrodes from short-circuiting and allow ions to pass through.

9. The capacitor according to claim 8, characterized in that Materials and structures of electrodes and housings; The electrode material is a porous active material with a specific surface area of ​​10-30m² / g, a pore size distribution of 5-500nm, and an electrode thickness of 10-100μm; the shell material is a composite structure of metal and polymer, the metal layer is one of aluminum, stainless steel or titanium, with a thickness of 0.05-0.5mm, and the polymer layer is one of polyethylene terephthalate (PET) and polyimide (PI), with a thickness of 0.03-0.2mm, to provide good mechanical strength and chemical stability.

10. The capacitor according to claim 8, characterized in that Capacitor performance parameters; The conductivity of the capacitor at 25°C is not less than 10mS / cm, and the rate of change of conductivity does not exceed ±20% in the temperature range of -20°C-60°C; during the charge and discharge process, the equivalent series resistance (ESR) does not exceed 0.05Ω, the charging time does not exceed 10 minutes at a 1C rate, and the discharge power density can reach 500-2000W / kg. After 5000 charge and discharge cycles, the capacitance retention rate is not less than 95%, which can meet the use requirements of high-performance capacitors in different environments.

Citation Information

Cited By

  • Temperature-resistant and voltage-resistant capacitor electrolyte composition and preparation method thereof

    CN121439516A

  • A temperature-resistant and pressure-resistant capacitor electrolyte composition and a preparation method thereof

    CN121439516B